Integrating Digital Media into Culturally Rooted Environmental Events to Promote Sustainable Lifestyle - Dhamayanti, Meilani; Sari, Siti Dewi Sri Ratna; Alfathi, Bintang Ridzky (Komunikator, 2025)
Deforestation remains one of Indonesia’s most pressing environmental challenges, driven primarily by plantation expansion, illegal logging, mining, and forest fires. Public awareness of deforestation risks is essential to support preventive efforts. Sedekah Hutan is a social campaign that combines environmental advocacy with cultural rituals, encouraging wider community participation. Although digital media offers significant potential to strengthen conservation education, its use in culturally rooted environmental campaigns often remains limited to event promotion. This study explores the current role of digital media in such campaigns and examines its potential for more transformative awareness-building.  Utilizing participatory and dialogical communication and media ecology theories, this qualitative research draws on participatory observation, interviews, and document analysis. Despite the limited use of digital media, it was important in communicating messages of cultural identity and care for the environment, especially for younger audiences. The event text drew on cultural conditions for its success, but carry-over awareness was reliant on working with stakeholder, and being more strategic in our engagement via digital media. Academically, this study contributes to environmental communication scholarship by connecting digital strategies with local wisdom. Practically, it offers insights for educators and campaigners to utilize social media beyond promotion—as a meaningful tool for long-term environmental advocacy.